Child pathology in the mendicants’ necropolis of El Burgo de Osma Cathedral (Soria, Spain) - Maria Dolorès Garralda; Jesus Herrerín; Bernard Vandermeersch (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The necropolis discovered in the Cloister of the El Burgo de Osma Cathedral (Soria, Northern Spain) consists of a group of 63 burials, with a total of 75 individuals, 55 adults, 4 youths and 16 children between 0 and 13 years old. Historical documents dating from the time when this necropolis was used (in the 17th and 18th centuries), point to this area as a cemetery for “…poor mendicants…”. The study of the pathologies of this human group corroborates these data, since several of the individuals suffered from a loss of movement preventing them from carrying out any physical work. This paper focuses on the paleopathological study of three infantile skeletons, particularly interesting since they reflect the hard living conditions and/or important alterations in the development of these beggar children.